PvMSP8 as a Novel Plasmodium vivax Malaria Sero-Marker for the Peruvian Amazon - Elizabeth Villasis; Katherine Garro; Angel Rosas-Aguirre; Pamela Rodriguez; Jason Rosado; Anthony Gave; Mitchel Guzman-Guzman; Paulo Manrique; Michael White; Niko Speybroeck; Joseph Michael Vinetz; Katherine Torres; et al. (Pathogens, 2021)
The measurement of recent malaria exposure can support malaria control efforts. This study evaluated serological responses to an in-house Plasmodium vivax Merozoite Surface Protein 8 (PvMSP8) expressed in a Baculovirus system as sero-marker of recent exposure to P. vivax (Pv) in the Peruvian Amazon. In a first evaluation, IgGs against PvMSP8 and PvMSP10 proteins were measured by Luminex in a cohort of 422 Amazonian individuals with known history of Pv exposure (monthly data of infection status by qPCR and/or microscopy over five months). Both serological responses were able to discriminate between exposed and non-exposed individuals in a good manner, with slightly higher performance of anti-PvMSP10 IgGs (area under the curve AUC = 0.78 [95% CI = 0.72–0.83]) than anti-PvMSP8 IgGs (AUC = 0.72 [95% CI = 0.67–0.78]) (p = 0.01). In a second evaluation, the analysis by ELISA of 1251 plasma samples, collected during a population-based cross-sectional survey, confirmed the good performance of anti-PvMSP8 IgGs for discriminating between individuals with Pv infection at the time of survey and/or with antecedent of Pv in the past month (AUC = 0.79 [95% CI = 0.74–0.83]). Anti-PvMSP8 IgG antibodies can be considered as a good biomarker of recent Pv exposure in low-moderate transmission settings of the Peruvian Amazon.